Plasma adipokines levels and functional fitness with concurrent combined aerobic and resistance training in older adults. - Eduardo Arend (2018)
Aging is associated with a decrease in cardiorespiratory and muscular fitness, flexibility, and also associated with the development of chronic diseases and lowchronic adipose tissue inflammation. Regular physical activity, specifically aerobic and resistance exercises, has been advised in older persons for the prevention of chronic diseases and functional limitations. However, only a limited number of studies have evaluated the impact of concurrent combined training, namely in adipokine levels of older adults. The purpose of this thesis was to further explore the evidence of the benefit of 8-month combined aerobic (AT) and resistance exercise (RT) in body composition (BC), physical fitness (PF) and adipokine profile of older community adults. Furthermore, the secondary aim this study was to investigate the relationships of some adipokines with lipid profile markers and BC parameters in older untrained adults. To achieve these objectives, three studies were performed: The first was a cross-sectional study with 34 untrained older adults, in order to investigate the relationship of two adipokines (leptin and adiponectin) with lipid profile and BC parameters. The second study aimed to investigate the effects of 8-month combined AT and RT on BC and PF in the older adults. The third study aimed to investigate the effect of 8-month combined AT and RT on plasma levels of five adipokines: leptin, resistin, adiponectin, PAI-1 and TNF-α, as well as the lipid profile in older adults. Based on the analysis of the results of the different studies presented in this thesis, it was possible to conclude that, in older adults, leptin is a body and lean mass dependent variable, and adiponectin is a variable dependent on abdominal fat mass and HDL cholesterol. It was also possible to state that 8-month combined AT and RT improves knee flexor isokinetic strength, muscle endurance and lower limb flexibility, but not adipokine plasma levels, lipid profile and glucose plasma levels. This thesis further reinforce that concurrent training seems to be a good strategy to increase muscular strength, endurance, as well as flexibility, and consequently, to maintain functional capacity during aging. Further additional randomized studies with larger samples sizes are needed to evaluate the impact of the combined training in the adipokine profile of older subjects.